2015
DOI: 10.1002/bit.25687
|View full text |Cite
|
Sign up to set email alerts
|

Integrated cell and process engineering for improved transient production of a “difficult‐to‐express“ fusion protein by CHO cells

Abstract: Based on an optimized electroporation protocol, we designed a rapid, milliliter-scale diagnostic transient production assay to identify limitations in the ability of Chinese hamster ovary (CHO) cells to produce a model "difficult-to-express" homodimeric Fc-fusion protein, Sp35Fc, that exhibited very low volumetric titer and intracellular formation of disulfide-bonded oligomeric aggregates post-transfection. As expression of Sp35Fc induced an unfolded protein response in transfected host cells, we utilized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 40 publications
3
75
0
Order By: Relevance
“…Such a bottleneck has been reported in CHO cells upon transient expression of an Fc-fusion protein (Johari et al, 2015) and EPO (Ku et al, 2008), although only EPO titer and not q p was reported for the latter example. In addition, a post-transcriptional bottleneck has been reported in stable MAb-producing CHO cells (S. J.…”
Section: Secretion Bottleneck and Er Stressmentioning
confidence: 82%
See 3 more Smart Citations
“…Such a bottleneck has been reported in CHO cells upon transient expression of an Fc-fusion protein (Johari et al, 2015) and EPO (Ku et al, 2008), although only EPO titer and not q p was reported for the latter example. In addition, a post-transcriptional bottleneck has been reported in stable MAb-producing CHO cells (S. J.…”
Section: Secretion Bottleneck and Er Stressmentioning
confidence: 82%
“…However, it has been shown that both CHO-and human-derived PDI can improve q p of human MAb-related r-proteins in CHO cells (Johari et al, 2015;Mohan et al, 2007;Pybus et al, 2014) (Table 1). Moreover, XBP-1S has been shown to increase volumetric productivity and q p in…”
Section: Effector Gene Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations in the secretion of recombinant proteins can impact both protein quality and yield, which can have a negative impact on downstream processes. Published reports have focused on the characterization of such ‘difficult‐to‐express’ recombinant proteins and described the modification of culture conditions 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or the design of appropriate cell/protein engineering strategies to overcome restrictions in their production 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26. However, little is known regarding the mechanisms underpinning poor recombinant protein production, particularly between proteins of high sequence similarity.…”
mentioning
confidence: 99%